North-South Standards Harmonization and International Trade - Disdier, Anne-Célia (The World Bank, 2013)
Recent years have seen a surge in economic integration agreements (EIAs) and the development of non-tariff measures (NTMs). As a consequence, a growing number of EIAs include provisions on NTMs. However, little attention has been given in the literature to the effects of NTM liberalization in the context of EIAs. In this paper, we focus on provisions for technical regulations and analyze whether the North-South harmonization of technical barriers affects international trade. Using a gravity equation, it tests whether, as a result of the deep integration associated with standards provisions included in the EIA, the Southern partners' trade expands with the North, but at the expense of their trade with non-bloc Southern partners. Empirical results provide strong support for this conjecture. Moreover, harmonization on the basis of regional standards negatively impacts the exports of developing countries to the North